Re-envisioning the heritage: Towards interpreting Mandalay’s multi-ethnicity through the lens of old city quarters - Shwin, Win Thant Win; Su , Su; Myo, Ohmmar; Aung, Tharaphy; Htay, Yamin; Thu, Soe Kyaw; Khaing, Nang Ei Ei; Zin, Kay (The Journal of City: Branding and Authenticity, 2024)
Mandalay is a multi-ethnic metropolitan city since the 19th century. Mandala symbolism is included in the city structure of Mandalay. In order to compete the Western power structure, Mandala was based in Mandalay’s city planning design which was planned in parallel with Yangon to go against the colonial power. It was quite transparent which ethnic groups were kept there, how they served the king and made cultural exchange among them and formed the national centre of cosmopolitan power and future multi-ethnic capital city. After the king was sent to exile and during the colonial period, these diverse cultural patterns were disturbed. It has undergone many changes since its creation, very slow and inappropriate ad-hoc developments after independence and only promoting the ancient Myanmar cultural heritage in past few decades. This paper highlights the multi-ethnic cultural heritages of Mandalay where Mandala symbolism is included in the the city planning concept. The unique Myanmar feature of Mandalay not only lies in its Buddhist and ritual believes, but also in its multi-ethnic groups’ rituals and meanings because of nearly 170 years of impermanence of different heritage of diverse ethnic groups. There are some parts still visible in daily fabric and activities. The paper concludes that the complexity of urban cultural heritage highlights that simple definition of urban identity does not make sense for Mandalay. Capturing Mandalay’s ethnic complexity is beyond the range of a single short paper. In this paper we will limit our discussion to a focused discussion of Islamic, Thai, Chinese, Christian and Manipuris and Assamese communities. Mandala’s cultural exchange was transparent and there are still the possibilities to be so in 2023 landscape.